Development of health education module for the school-based health education intervention to improve the knowledge, attitude and practices on pediculosis capitis - Mohd Tohit, Nor Faiza; Lekhraj, Rampal; Lye, Munn Sann; Muhamad Saliluddin, Suhainizam (Department of Community Health, Faculty of Medicine and Health Sciences, University Putra Malaysia, 2018)
Background: Pediculosis capitis is a common infestation among the school-aged group. Necessary intervention must be taken to prevent and manage the problem. A full study using cluster randomized control trial is proposed to assess the effectiveness of a health education module on the knowledge, attitude and practices on Pediculosis capitis among government primary school students. If the intervention is effective, it can be generalized to the whole primary schools across the country. Therefore, this paper will discuss on the development of a school-based health education intervention to improve the knowledge, attitude and practices on Pediculosis capitisamong the government primary school students. Materials and Methods: Literature review was done to examine the prevalence of Pediculosis capitis and its determinants. Based on the findings, a health education intervention module based on KAP Model was developed for the implementation at a school level. Contribution by the panel of experts was attained for the development of the module. Validation of the module was carried out to ensure it is suitable to be implemented and will be effective in preventing and managing Pediculosis capitis. Expected Result: The health education intervention is effective to improve the knowledge, attitude and practices on Pediculosis capitis of the respondents as compared to baseline. Conclusion:Preventing Pediculosis capitis and controlling its risk factors by a well-developed health education module will help to obtain the desired outcome which is the reduction of Pediculosis capitis and improvement of knowledge, attitude and practice on Pediculosis capitis among the respondents.